Analisis Kebijakan Pengelolaan Sumberdaya Lahan pada Cagar Alam Pegunungan Cycloop (Analysis of Land Management Policy Resources at Preserve Cycloop Mountain) - Yaconias Maintindom; Andry Indrawan; Hariadi Kartodihardjo (Institut Pertanian Bogor (IPB University), 2006)
For that this Research aim to (a) analyses the optimal exploiting alternative to area preserve cycloop mountain (b) know the clean water source and economic value and (c) compile the strategy of development CAPC. Result of research indicate that, (a) CAPC more optimal done by activity of conservation and tourism B/C = 1, settlement and infrastructure 0, 965 or